Fast Food Nation - Maria Hussain (International Institute of Islamic Thought, 2002)
Combining in-depth historical and socio-political analyses of the American food industry with an easy-flowing language style, Fast Food Nation is nearly impossible to put down. Mind-boggling in scope, yet as intimate as one's own kitchen, this book allows the reader to grasp the true horror of the global food situation. Schlosser provokes both laughter and tears, ultimately inspiring the reader to engage in the "higher jihad" of controlling one's appetite with the understanding of how personal consumer choices have political consequences.